Response of Wheat to a Multiple Species Microbial Inoculant Compared to Fertilizer Application - Assainar, Salmabi K.; Abbott, Lynette K.; Mickan, Bede S.; Whiteley, Andrew S.; Siddique, Kadambot H. M.; Solaiman, Zakaria M. (Frontiers in Plant Science, 2018)
Microbial inoculants, including those formed from multiple species, may have dual functions as biostimulants and/or biocontrol agents, and claimed agricultural benefits are instrumental for regulatory categorisation. Biostimulants include commercial products containing substances or microorganisms that stimulate plant growth. Biostimulant microbes can be involved in a range of processes that affect N and P transformations in soil and thus influence nutrient availability, and N and P fertilizers can influence soil microbial diversity and function. A glasshouse experiment was conducted to investigate the effect of a multiple species microbial inoculant relative to a rock-based mineral fertilizer and a chemical fertilizer on wheat growth and yield, and on microbial diversity in the rhizosphere. The microbial inoculant was compared to the mineral fertilizer (equivalent to 5.6 kg N ha-1 and 5.6 kg P ha-1), and to the chemical fertilizer applied at three rates equivalent to: (i) 7.3 kg N ha-1 and 8.4 kg P ha-1 as recommended for on-farm use, (ii) 5.6 kg N ha-1 and 6.5 kg P ha-1 which matched the N in the mineral fertilizer, and (iii) 4.9 kg N ha-1 and 5.6 kg P ha-1 which matched P content in the mineral fertilizer. Despite an early reduction in plant growth, the microbial inoculant treatment increased shoot growth at maturity compared to the control. Similarly, grain yield was higher after application of the microbial inoculant when compared to control, and it was similar to that of plants receiving the fertilizer treatments. Using 16S rRNA sequencing, the microbial inoculant and fertilizer treatments were shown to influence the diversity of rhizosphere bacteria. The microbial inoculant increased the relative abundance of the phylum Actinobacteria. At tillering, the proportion of roots colonized by arbuscular mycorrhizal (AM) fungi increased with the microbial inoculant and mineral fertilizer treatments, but decreased with the chemical fertilizer treatments. At maturity, there were no treatment effects on the proportion of wheat roots colonized by AM fungi. Overall, the multiple species microbial inoculant had beneficial effects in terms of wheat yield relative to the commercial mineral and chemical fertilizers applied at the level recommended for on-farm use in south-western Australia.